PERMASALAHAN ABORSI DAN PENEGAKAN HUKUMNYA - Agustanti, Rosalia Dika (Res Judicata, 2022)
The purpose of this study is to examine the implementation of abortion in Indonesia, especially for women who are victims of rape. The research method used is normative juridical. The results showed that a person could have an abortion when pregnancy occurs due to rape which can cause psychological trauma with the condition that the abortion is carried out before six weeks of pregnancy, calculated from the first day of the last menstruation. It is still found that abortions are carried out when the pregnancy is more than six weeks old. Not a few of those who carry out abortions are sentenced to criminal penalties, can say that the application of legal protection guaranteed by the law is far from perfect, especially law enforcement that is less partial to rape victims who choose the abortion route does not reflect the sense of justice, certainty and benefit be a legal goal. Therefore, legal protection for abortionists who are victims of rape must consider the best interests of the victims, and this can be realized when the Government carries out its obligations to protect and prevent abortions.